THE CORRELATION BETWEEN EPICARDIAL FAT THICKNESS BASED ON MULTI SLICE COMPUTED-TOMOGRAPHY SCAN THORAX WITH WAIST CIRCUMFERENCE AND BODY MASS INDEX ON DYSLIPIDEMIA NON-DIABETES MELLITUS SUBJECT - Yenny Wendy; Mirna Muis (Nusantara Medical Science Journal, 2018)
Introduction : Epicardial fat is visceral fat that plays a role in cardiovascular disease. Dyslipidemia non-diabetes mellitus can be found in both obese and non-obese patients. Measurement of waist circumference and BMI can assess central and peripheral obesity. The study aims to finding out the correlation between epicardial fat thickness based on MSCT scan Thorax with waist circumference and BMI on dyslipidemia non-diabetes mellitus subject. Method: There were 57 research samples of 28 to 70 years old who had dysfunction lipid profile. The most samples were found in the age group of 45-64 years with epicardial fat ranges from 2.80 to 10.80 mm and mean of 6.37 mm. Data were analysed by Mann-Whitney and Spearman correlation test. Result: There was a significant correlation between waist circumference and epicardial fat (r = 0.286, p = 0,031). There was no difference in mean of epicardial fat thickness by sex. There was no correlation between sex, and BMI with epicardial fat. Conclusion: There is a correlation between waist circumference and epicardial fat that may be affected by several factors in patients with dyslipidemia non-diabetes mellitus.